Airway challenges in Pierre Robin Syndrome children with cleft conditions in a surgical mission - Annu Theagrajan; A Anbu Muruga Raj; Beulah Shekinah Elango; Nalini Kotekar (Journal of Krishna Institute of Medical Sciences University)
Surgical missions are often conducted in outreach areas where facilities are often not as advanced as in an institution. Excellent team coordination, detailed planning, and good communication are necessary for a successful outcome. Unfamiliar work environment, new acquaintances within the team, and language barriers at the mission site are some of the challenges often faced. Careful patient selection is crucial in a mission setup as most complications can be traced back to the preanaesthetic check and preoperative preparedness. We describe airway management strategies (airway assessment, mask ventilation, intubation options, and the postoperative airway plan) contrived by our anaesthesia team at one such surgical mission where four children with Pierre Robin Syndrome and incomplete cleft palate (involving posterior hard palate and complete soft palate)were successfully operated.